THE INFLUENCE OF COMPENSATION PROVISION AND WORKING ENVIRONMENT ON THE PERFORMANCE OF VILLAGE APPARATUS WITH WORK MOTIVATION AS AN INTERVENING VARIABLE (Case Study on Sugar Village Officials) - Rumiris Siahaan; Rakhmawati Purba; Rizki Wulanita Batubara; Shofyan Roni; Pinondang Nainggolan (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The aim of this research is to see the effect of compensation and the work environment on the performance of village officials with work motivation as an intervening variable''. (case study on Pergulaan village officials). The type of research used in this research is quantitative. Quantitative methods are a type of research that has a systematic, planned and structured approach from the start until the creation of the research design. The nature of the research in this study is replication. This research uses multiple linear analysis methods, multiple linear analysis methods are used to test the influence of two or more independent (explanatory) variables on the dependent variable. The results of the research show that compensation influences the work motivation of Pergulaan village officials, the work environment influences the work motivation of Pergulaan village officials, compensation influences the performance of Pergulaan village officials, the work environment influences the performance of Pergulaan village officials, motivation influences the performance of Pergulaan village officials, motivation can mediating the relationship between compensation and the performance of Pergulaan village officials, work motivation can mediate the relationship between the work environment and the performance of Pergulaan village officials.